How to Improve Sustainability Performance Through Human Resource Management and green Supply Chain Management Strategies in the industrial Manufacturing Sector - Dwita, Febrisi; Supardi, Supardi; Trigunadi Santoso, Adrianus; Dexon, Christopher (IJBLE Scientific Publications Community Inc., 2024)
This research investigates the impact of Green Human Resource and Green Supply Chain strategies on improving sustainable performance in the manufacturing industry. The main focus of this research is to understand how the implementation of these green strategies can improve a company's operational efficiency and productivity. This approach includes human resource management with a focus on environmental sustainability and supply chain optimization to minimize environmental impacts. The research methodology involved quantitative data analysis measuring the impact of green strategies on sustainable performance using random sampling. The research technique was carried out by means of observation, distributing questionnaires and processing data using SEM-AMOS. The sample used was 310 respondents in manufacturing companies located in the Bekasi area. The results of this study are expected to provide valuable insights for the manufacturing industry in facing sustainability challenges and increasing competitiveness through environmentally friendly business practices